Mawqif Nahdat al-'Ulamā' min Ḥarakat al- Tabshīr al-Masīhī bi Indūnīsīyā - Nursamad, Nursamad (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1997)
Islam as a religion is to be critical of religion two predecessors, both to Jews and Christians. However, according to NU, the Islamic view of Christianity is more positive than the views about Jews. That's because the Jewish religion is seen in relationship with God has strayed too far. A positive attitude of Islam towards Christianity, according to NU, can be seen in the statement of the Koran that praises that among Christians there are monks and priests who are not arrogant. But NU deplore the ways and practices of Christianization in Indonesia are judged contrary to the positive attitude of Islam towards ChristianityDOI: 10.15408/sdi.v4i3.774